PNEUMATIC VITREOLYSIS FOR RELIEF OF VITREOMACULAR TRACTION. Issue 10 (October 2017) - Chan, Clement K.; Crosson, Jason N.; Mein, Calvin E.; Daher, Noha
Abstract : Purpose: To evaluate the outcome of perfluoropropane (C3 F8 ) gas injection for symptomatic vitreomacular traction (VMT) with or without Stage 2 macular hole (MH). Methods: A retrospective review of eyes with VMT treated with 0.3 mL of C3 F8 gas was performed. Patients avoided the supine position until gas resolution. Patients with small MH maintained partial face-down positioning. Results: Forty-nine consecutive patients (50 eyes) with symptomatic VMT underwent pneumatic vitreolysis between 2010 and 2016. A posterior vitreous detachment developed in 43 eyes (86.0%) after a single gas injection, at a median of 3.0 weeks. Twenty-eight of 35 eyes (80.0%) with VMT only and all 15 eyes (100%) with a small Stage 2 MH developed a posterior vitreous detachment, with MH closure in 10 of 15 eyes (66.7%). Median baseline and last best spectacle–corrected visual acuities were 20/50 and 20/40, respectively ( P < 0.001). Mean follow-up time was 11.1 ± 9.9 months. Rate of posterior vitreous detachment was reduced with presence of diabetes mellitus (25%) and with thick cellophane membrane (50%). Univariate analysis showed increased VMT release for eyes with VMT extent within 1 disk area (χ 2 = 13.1, P = 0.002), eyes with absence of diabetes mellitus (χ 2 = 8.8, P = 0.007), and eyes with Stage 2 MH (χ 2 = 5.47, P = 0.019); there was a trend between success and lack of thick cellophane membrane (χ 2 = 3.32, P = 0.068). Results using logistic regression also showed younger age ( P = 0.012), followed by better baseline best spectacle–corrected visual acuity ( P = 0.044), lack of diabetes mellitus ( P = 0.077), and female gender ( P = 0.045) to be predictors of increased VMT release. One VMT-only eye formed a MH and another VMT-only eye developed a retinal detachment. Both eyes responded to vitrectomy. Conclusion: Pneumatic vitreolysis with limited face-down position is a viable option for treating VMT with few adverse events. More studies are needed to elucidate its indications, benefits, and risks. Abstract : Pneumatic vitreolysis with C3 F8 gas is effective in releasing focal vitreomacular traction in a high percentage of eyes with few adverse events, especially with limited vitreomacular traction (within 1 disk area), lack of thick cellophane membranes, no diabetes mellitus, younger age (mean age of 69.1 years vs. 78.1 years), better baseline best spectacle–corrected visual acuity (mean of 20/50 vs. 20/66), small Stage 2 macular hole, and female gender.